2017
DOI: 10.4149/bll_2017_040
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-370 suppresses the retinal capillary endothelial cell growth by targeting KDR gene

Abstract: MicroRNA-370 inhibits the expression of KDR gene resulting in retinal capillary endothelial cell growth inhibition and apoptosis, which could be of value in the treatment of retinal neovascularization (Tab. 1, Fig. 5, Ref. 27).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The proliferation of HUVECs and formation of capillary‐like structures can be promoted by miR‐370 via inhibiting the expression of forkhead box 1 and maternally expressed gene 3 . But in retinal capillary endothelial cell, miR‐370 was reported to induce growth inhibition and apoptosis by reducing the expression of kinase insert domain‐containing receptor gene . Such discrepancies mechanism could be due to the contexts of different endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation of HUVECs and formation of capillary‐like structures can be promoted by miR‐370 via inhibiting the expression of forkhead box 1 and maternally expressed gene 3 . But in retinal capillary endothelial cell, miR‐370 was reported to induce growth inhibition and apoptosis by reducing the expression of kinase insert domain‐containing receptor gene . Such discrepancies mechanism could be due to the contexts of different endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-370 has been experimentally validated to target ENG in ovarian cancer cells [ 75 ], yet its role in EC function and angiogenesis is unclear, as multiple reports have demonstrated conflicting evidence. Overexpression of miR-370 inhibited proliferation, migration and tube formation in human dermal microvascular ECs, retinal capillary ECs and HUVECs [ 76 , 77 ]. In contrast, miR-370 overexpression was shown to promote HUVEC proliferation, migration and tube formation to facilitate healing after finger amputation [ 78 ].…”
Section: Circulating Mir Biomarkers In Hhtmentioning
confidence: 99%
“…Previous studies found that miR-126, -296, and the -23-27-24 cluster exert proangiogenic effects (15)(16)(17), whereas miR-191, -92a, and -26a inhibit the angiogenic activity of ECs (18)(19)(20). miR-370-3p (miR-370), which is located in the delta-like homolog 1-iodothyronine deiodinase 3 (DIO3) region on human chromosome 14 (21), has been reported to be expressed in several types of ECs (22,23). However, the function of miR-370 in regulating the angiogenic activity of ECs still needs to be clarified.…”
mentioning
confidence: 99%